2007
DOI: 10.1037/0021-9010.92.6.1696
|View full text |Cite
|
Sign up to set email alerts
|

Web-based recruitment: Effects of information, organizational brand, and attitudes toward a Web site on applicant attraction.

Abstract: Recruitment theory and research show that objective characteristics, subjective considerations, and critical contact send signals to prospective applicants about the organization and available opportunities. In the generating applicants phase of recruitment, critical contact may consist largely of interactions with recruitment sources (e.g., newspaper ads, job fairs, organization Web sites); however, research has yet to fully address how all 3 types of signaling mechanisms influence early job pursuit decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
285
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(311 citation statements)
references
References 67 publications
(132 reference statements)
14
285
0
12
Order By: Relevance
“…As existing literature indicated that hard navigation, incomplete information, rigid structure and boring website feature can affect users mood and perception regarding corporate brand (Brahmana, 2013;Palmer, 2002;Agarwal & Venkatesh, 2002;Cober et al, 2003;Huang et al, 2012;Allen et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As existing literature indicated that hard navigation, incomplete information, rigid structure and boring website feature can affect users mood and perception regarding corporate brand (Brahmana, 2013;Palmer, 2002;Agarwal & Venkatesh, 2002;Cober et al, 2003;Huang et al, 2012;Allen et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between information, organisational brand and attitudes toward website attraction for applicants is argued to be an important area to explore, as website usability, aesthetics, accuracy and richness of job information and organisational information somehow impact viewers' attitudes towards organisational recruitment websites (Allen et al, 2007;Maurer et al, 2007). Furthermore, internet based selection procedures can also have positive impact on perception of company image among potential candidates (Anderson, 2003).…”
Section: Website Features Affect a Potential Job Applicant Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that e-recruiting can dramatically reduce recruiting cycles and costs (Cober, Brown, Blumenthal, Doverspike, & Levy, 2000). However, beyond improving efficiency, e-recruiting can also help improve recruiting outcomes such as applicants' perception of the firm and their intention to apply for a position with the firm (Allen, Mahto, & Otondo, 2007).…”
Section: E-recruitmentmentioning
confidence: 99%
“…In today's global and highly competitive marketplace, recruitment 'has emerged as a key antecedent of organisational effectiveness' (Allen, Mahto, & Otondo, 2007, p. 1696. This talent acquisition process is complex and costly involving many decisions on the part of both the employer and potential employee.…”
Section: Introductionmentioning
confidence: 99%